The Role of Hedonistic Buying Motivation, Shopping Lifestyle, and Brand Ambassador on Purchase Intentions of Blibli.com Marketplace Users in Kuningan Regency - Wachjuni; Masruroh, Rina; Rahmawati , Aulia Nur; Maulana, Yasir (Asosiasi Ahli Administrasi Indonesia, 2024)
The aim of this research was to investigate the impact of Hedonistic Shopping Motivation, Shopping Culture, and Brand Ambassador on the Purchase Intention of Blibli.com Marketplace consumers in Kuningan Regency. The method is descriptive-verificative analysis. The study population comprised 150 Blibli.com Marketplace users, and the data was collected through a questionnaire and examined through the application of multiple linear regression. The findings indicated that Hedonic Shopping Motivation, Shopping Lifestyle, and Brand Ambassador collectively and individually exerted a significant influence on purchase intention. The findings imply that Hedonic Shopping Motivation, Shopping Lifestyle, and Brand Ambassador significantly influence purchase intention. To boost purchase intent, companies should create enjoyable shopping experiences, align products with consumer lifestyles, and use relevant brand ambassadors effectively.